Mutated p53 Promotes the Symmetric Self-Renewal of Cisplatin-Resistant Lung Cancer Stem-Like Cells and Inhibits the Recruitment of Macrophages - Yu Xu; Zhi Xu; Qi Li; Liang Guo; Yao Wang; Jianchun Zhou; Guansong Wang; Yuliang Liu (Journal of Immunology Research)
It has been proposed that mutant p53 is correlated with the recurrence of lung cancer. Recently, a small population of cells with asymmetric or symmetric self-renewal potential has been identified in lung cancer, which was termed as cancer stem-like cells (CSCs) and was speculated to be the reason for cancer recurrence after chemotherapy. In this study, we used lung cancer cell lines with different TP53 backgrounds to elucidate the potential role of mutant p53 in regulating lung CSC self-renewal and on lung cancer recurrence. Cisplatin-resistant lung cancer cells with different TP53 backgrounds were generated in vitro by exposing A549, H460, and H661 lung cancer cell lines repeatedly to cisplatin. CD44+/CD90+ stem-like cells were identified in above cisplatin-resistant lung cancers (termed as cisplatin-resistant lung cancer stem-like cells, (Cr-LCSCs)) and stained with PKH26 dye which was used to define the self-renewal pattern. The proportion of symmetric divisions was significantly higher in Cr-LCSCs with mutant (mt) p53 compared with Cr-LCSCs with wild-type (wt) p53, and forced expression of mt p53 promoted the symmetric division of Cr-LCSCs. Furthermore, fewer macrophages accumulated in subcutaneously implanted xenografts consisting of mt p53 Cr-LCSCs compared with wt p53 Cr-LCSCs. These results indicated that mt p53 might accelerate the recurrence of lung cancer by regulating the self-renewal kinetics of Cr-LCSCs as well as the recruitment of macrophages.